The Mediating Role of Policy-Related Factors in the Relationship between Practice of Waste Generation and Sustainable Construction Waste Minimisation: PLS-SEM - Mohammed, M. (MDPI, 2022)
As the construction industry grows, it produces large volumes of construction waste, which has a tremendous environmental impact and generates public concern in the neighbouring towns. The construction industry generates a significant volume of waste and faces a challenge with poor construction waste minimisation in order to prevent adverse environmental and dumping impacts worldwide. In developing countries, regional waste management systems have increased problems. Environmental pollution (air, water, and soil) and human health issues are caused by waste produced in a country as a result of different cultural, social, and religious activities. Prior studies were reviewed to choose dimensions and items for the data gathering instrument. A pilot test was conducted to identify potential questionnaire adjustments, and hypotheses were tested using structural equation modelling (SEM). A total of 220 Malaysian construction professionals answered the survey, which yielded the results. Five hypotheses have direct correlations based on the findings, three of which have a significant effect. Furthermore, the findings reveal that policy-related factors mediate the relationship between improving factors and sustainable construction waste minimisation. In contrast, they did not mediate the relationship between current practices/generation and sustainable construction waste management. The established framework can help improve construction waste management and help achieve global sustainable development goals. The data reveal that adopting preventive plans to reduce construction waste is one of the most important aspects of enhancing profitability. This study could aid construction industry players in evaluating waste management components during the construction and design stages of a building project. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.